2019
DOI: 10.1049/iet-map.2019.0392
|View full text |Cite
|
Sign up to set email alerts
|

Pair of diagonal slots loaded low‐profile circularly polarised patch antenna with wide 3 dB axial ratio beamwidth

Abstract: A low‐profile circularly polarised (CP) antenna with wide 3 dB axial ratio beamwidth (ARBW) is proposed in this study. The possibilities of widening the 3 dB ARBW of single diagonal slot‐loaded conventional CP antenna have been explored successfully by incorporating a pair of rectangular slots along the diagonal line of a square patch antenna. The design parameters and the symmetrical arrangement of this pair of slots across the centre of the patch are crucial to adjust and achieve the wide 3 dB ARBW with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Initially, a conventional approach involving a crossed-shaped slot [28] at the center of the patch is conceived to design a planar circular-shaped CP antenna, as shown in Fig. 1(a).…”
Section: Design Strategies and Working Principle Of The Proposed Cp A...mentioning
confidence: 99%
“…Initially, a conventional approach involving a crossed-shaped slot [28] at the center of the patch is conceived to design a planar circular-shaped CP antenna, as shown in Fig. 1(a).…”
Section: Design Strategies and Working Principle Of The Proposed Cp A...mentioning
confidence: 99%
“…Due to this the reported design has larger patch area and lower gain as well. Using diagonal slots on thinner substrate circular or rectangular patches, CP design offering higher AR beam width is reported [38][39][40]. However, those designs offer single band CP response with lower AR BW and thus cannot find applications in frequency and polarization agile systems.…”
Section: Parametric Design Formulation For Modified ψ-Shape Msamentioning
confidence: 99%
“…The generation of CP radiation depends on the insertion of appropriate fractional slotted area in the antenna. It is observed that an antenna with a <1% (≈ 0.7%) fractional slotted area [17] radiates linearly polarized waves. However, the 3-dB ARBW of CP radiation is tuned with the placement of slotted structure in the antenna.…”
Section: Antenna Configuration and Design Analysismentioning
confidence: 99%
“…Strips based scheme on slotted patch is examined to study a CP antenna for beamwidth enhancement [16]. A critical study on the slotted fractional part concerning the patch is investigated for beamwidth clarification of CP antenna [17]. In [18], the beamwidth of CP antenna is presented as function of mutual coupled field between slotted structures.…”
Section: Introductionmentioning
confidence: 99%